Esther e Polaquinha: transgressão e prostituição nas narrativas de Moacyr Scliar e Dalton Trevisan - Calixto, Lunara Abadia Gonçalves (2021)
Female sexuality, over the centuries, has been subject to patriarchal controls and restrictions. In fact, although there is supposedly a freedom in the approach to that theme in contemporaneity, taboos and prohibitions still persist in different contexts, mainly religious ones. Despite the prescriptions that determine decorum and submission for women, who must behave as "respectable", there is that one who, at least technically, has the possibility of transgressing the sexual norms of behavior: the prostitute. Considered as a corrupt woman, who must redeem herself from her actions, the figure of the prostitute is present in literary representations of romantic conceptions. In a different perspective, the characters Esther, from O ciclo das águas, by the author Moacyr Scliar, and Polaquinha, from the work A Polaquinha, by Dalton Trevisan, are presented. These protagonists, belonging to different historical and sociocultural contexts, have points in common, as they were forced into prostitution due to the stereotype of polacas attributed to them (white women, usually blonde, who were sex slaves of international prostitution networks), in addition to challenging their gender roles in pursuit of sexual pleasure. Thus, this thesis aims to analyze the figure of the prostitute from the characters Esther and Polaquinha, observing the aspects of both narratives that relate to commercialized female sexuality and, concomitantly, to the erotic experiences that trigger the empowerment and decay of protagonists. They had their pinnacle and ruin in prostitution, but, before their decline, they resisted the impositions and transgressed the regulations determined to them in the patriarchal society from which they came. Thus, the study of these works cited presents the possibility of elucidating a theme permeated by stereotypes and stigmas; moreover, knowing the trajectory of these prostitute characters is also having access to representations of the feminine from the perspective of Western culture and the Judeo-Christian tradition, which still have, significantly, a misogynist view.